Onesnaženost ledenika Baltoro kot posledica turistične dejavnosti - Mrak, Irena (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2007)
Mass tourism in the world's high mountain areas is already having negative environmental impacts. In the case study area of the Baltoro Glacier (Karakorum Mountains, Pakistan) the main motive is a view or even an ascent of K2 (8611m) as well as the surrounding high mountains. The field work carried out was dedicated to pollution sources in the area, as well as to the pollution rate of the wider Baltoro Glacier area.
Keywords: Karakorum; Pakistan; Baltoro; ledeniki; glaciologija; tourism; turizem; onesnaževanje; pollution; onesnaženost